The architecture social media and online newspaper credibility measurement for fake news detection - Rakhmat Arianto; Harco Leslie Hendric Spits Warnars; Edi Abdurachman; Yaya Heryadi; Ford Lumban Gaol (Universitas Ahmad Dahlan, 2019)
Social media is one of the communication media favored by people in the world, especially in Indonesia. This is evidenced by the results of the APJII survey which shows that the majority of Indonesians use social media in their daily activities. One of the advantages of social media is the dissemination of information faster than conventional media so that the quality of information disseminated is lower than conventional media due to the process of disseminating information not through the filter process. By measuring the level of credibility of the online newspaper based on the time credibility, website credibility, and message credibility factors and measuring the level of credibility on social media based on the time credibility, Social Media Credibility, and Message Credibility factors with different levels of weight, it will produce a news likelihood level it's fake news or facts.